Pride of a nation : a celebration of the U.S. Women's National Soccer Team - Oxenham, Gwendolyn (Ten Speed Press, 2022)
Drawing from extensive photo and print archives, this first official history of the U.S. Women's National Soccer Team pays tribute to one of the most beloved teams in sports, revisiting their historic four World Cup titles and four Olympic gold medals, as well as unforgettable players across the generations.